1997
DOI: 10.1016/s0378-1135(97)00144-2
|View full text |Cite
|
Sign up to set email alerts
|

Passive protection of neonatal calves against bovine coronavirus-induced diarrhea by administration of egg yolk or colostrum antibody powder

Abstract: The protective effect of egg yolk and colostrum powders prepared from hens and cows vaccinated with inactivated bovine coronavirus (BCV) antigen was evaluated in a challenge model with a virulent BCV strain. Twenty three calves from BCV-free herds were randomly divided into control and several treatment groups. All calves were orally challenged with 1 x 10(9) TCID50 of the virulent Kakegawa strain of BCV at 24 to 36 h after birth. Calves in treatment groups received either egg yolk powder or cow colostrum cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 5 publications
(5 reference statements)
2
51
0
1
Order By: Relevance
“…led to reductions in ruminal lactate concentration and target bacteria (Shu et al, 1999). Similarly, passive immunization achieved by feeding colostrum or eggs successfully prevented bovine coronavirus diarrhea (Ikemori et al, 1997) in bottle-fed calves. Feeding avian antibodies is a possible alternative because immunoglobulin Y, the main source of immunoglobulins in avian antibodies, is resistant to heat, acid digestion, and proteolysis (Shimizu et al, 1988).…”
Section: Introductionmentioning
confidence: 93%
“…led to reductions in ruminal lactate concentration and target bacteria (Shu et al, 1999). Similarly, passive immunization achieved by feeding colostrum or eggs successfully prevented bovine coronavirus diarrhea (Ikemori et al, 1997) in bottle-fed calves. Feeding avian antibodies is a possible alternative because immunoglobulin Y, the main source of immunoglobulins in avian antibodies, is resistant to heat, acid digestion, and proteolysis (Shimizu et al, 1988).…”
Section: Introductionmentioning
confidence: 93%
“…Vega et al (2011) reported that supplementing newborn calves; diets for the first 14 days of the life with egg yolk, represents a promising strategy to prevent bovine rotavirus diarrhea. Ikemori et al (1997) indicated that the orally administered egg yolk of immunized hens with bovine coronavirus and colostrums powders protected against bovine coronavirus which induced diarrhea in neonatal calves.…”
Section: Discussionmentioning
confidence: 99%
“…Ikemori et al (1997) vaccinated 10 white Leghorn hens with NCDC antigen containing about 10 8.5 TCID 50 /ml with 0.3% formalin. The antigen was mixed with an equal volume of oil adjuvant with 5% mannide monooleate and 1.0 ml of the mixture was injected intramuscularly.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies from hens vaccinated with Salmonella Enteritidis, among others, significantly suppressed in vitro production of the toxin compared to non-immunized yolk (Sugita-Konishi et al 1996). Vaccination of hens could be better solution than vaccination of cows, because large scale production is easier and there is not much difference because of similar antibody response (neutralization titers 1:5120) in vaccinated hens and cows (Ikemori et al 1997).…”
Section: Discussionmentioning
confidence: 99%